Kidney injury owing to Streptococcus pneumoniae infection in critically ill infants and children: report of four cases. (1st October 2016) - Piastra, M.; Tempera, A.; Luca, E.; Buffone, E.; Cafforio, C.; Briganti, V.; Genovese, O.; Marano, M.; Rigante, D.; ,
Abstract : Streptococcus pneumoniae sepsis has high morbidity, particularly if complicated by renal injury. Four patients with S. pneumonia invasive infections complicated by renal disorders are presented. The first case was an 18-month-old girl with pneumococcal empyema complicated by haemolytic uraemic (HUS) syndrome. She made a full recovery after mechanical ventilation, inotropic support and haemodiafiltration. The second was a 4-year-old boy who presented with acute post-infectious glomerulonephritis associated with bilateral pneumococcal pneumonia. He too made a complete recovery. The third was a newborn girl with pneumococcal meningitis complicated by acute respiratory distress syndrome and acute renal failure. The fourth patient was an 8-month-old boy with pneumococcal pneumonia and meningitis complicated by HUS and with fulminant thrombotic thrombocytopenic purpura. Despite full support including mechanical ventilation and haemodiafiltration, he died 4 days after admission. On follow-up, all three survivors recovered completely from their pulmonary symptoms and had normal renal function and cardio-circulatory status in the mid-term.